Influence of manganese ions on elastic and spectroscopic properties of ZnO doped novel calcium fluorophosphate bio active glasses. (29th October 2021) - Chand, N Rama Krishna; Sudhakar, B K; Ravikumar, G; Rao, G Srinivasa; Rao, Ch Srinivasa
Abstract: The glass system 20CaF2 -20ZnO-(60-x)P2 O5 :xMnO with 0 ≤ x ≤ 5.0 was prepared and investigated. The structural changes induced by the addition of MnO in the glass network were explained by using physical, elastic, thermal, chemical durability and spectroscopic studies. Results indicate that with the increase of concentration of MnO content from 1 to 5 mol% the parameters like density, pH of the immersion liquid, elastic moduli and glass characteristic temperatures increases. While the dissociation rate, the Poisson's ratio and volume per mol decreases and signifying the increased mechanical strength of the prepared glasses. FTIR spectral analysis predicts that all the specific vibrational bands of phosphate bonds like bridging oxygen with phosphorous action, linkages like P-O-P, O-P-O and the crossed linkages like P-O-Mn & P-O-Zn are affected by the incorporation of MnO in the glass matrix. The changes observed in peak positions and intensities of all vibrational bands of IR spectra and optical absorption spectra confirm that manganese ions behaves as a glass former and also as a glass modifier depending on the concentration of MnO. The analysis of the optical absorption spectra of the glasses in particular the crystal field and interelectronic repulsion parameters shows that manganese ions are predominantly occur in the divalent state and occupy tetrahedral sites in the glass matrix when the concentration of MnO in the CaF2 -ZnO-P2 O5 glasses exceeds 1.0 mol%.